A crossbar resistance switching memory readout scheme with sneak current cancellation based on a two-port current-mode sensing. (31st October 2016) - Bae, Woorham; Yoon, Kyung Jean; Hwang, Cheol Seong; Jeong, Deog-Kyoon
Abstract: This paper describes a novel readout scheme that enables the complete cancellation of sneak currents in resistive switching random-access memory (RRAM) crossbar array. The current-mode readout is employed in the proposed readout, and a few critical advantages of the current-mode readout for crossbar RRAM are elucidated in this paper. The proposed scheme is based on a floating readout scheme for low power consumption, and one more sensing port is introduced using an additional reference word line. From the additional port, information on the sneak current amount is collected, and simple current-mode arithmetic operations are implemented to cancel out the sneak current from the sensing current. In addition, a simple method of handling the overestimated-sneak-current issue is described. The proposed scheme is verified using HSPICE simulation. Moreover, an example of a current-mode sense amplifier realizing the proposed cancelling technique is presented. The proposed sense amplifier can be implemented with less hardware overhead compared to the previous works.